Prognostic significance of interleukin-17A-producing colorectal tumour antigen-specific T cells - Thomson, Amanda (Br J Cancer, 2021)
BACKGROUND: The T cell cytokine profile is a key prognostic indicator of post-surgical outcome for colorectal cancer (CRC). Whilst T(H)1 (IFN-γ(+)) cell-mediated responses generated in CRC are well documented and are associated with improved survival, antigen-specific T(H)17 (IL-17A(+)) responses have not been similarly measured. METHODS: We sought to determine the cytokine profile of circulating tumour antigen-(5T4/CEA) specific T cells of 34 CRC patients to address whether antigen-specific IL-17A responses were detectable and whether these were distinct to IFN-γ responses. RESULTS: As with IFN-γ-producing T cells, anti-5T4/CEA T(H)17 responses were detectable predominantly in early stage (TNM I/II) CRC patients. Moreover, whilst IL-17A was always produced in association with IFN-γ, this release was mainly from two distinct T cell populations rather than by ‘dual producing’ T cells. Patients mounting both tumour-specific T(H)1(+)/T(H)17(+) responses exhibited prolonged relapse-free survival. CONCLUSIONS: Tumour antigen-specific T(H)17 responses play a beneficial role in preventing post-operative colorectal tumour recurrence.